Comorbidity pattern of personality disorder and reliability of diagnostic and statistical manual-111-R and international classification of diseases-10 in assessing personality disorders - Enyidah, Nonyenim Solomon; Nonye-Enyidah, Esther Ijeoma (International Journal of Advances in Medicine, 2020)
Background: Comorbidity of personality disorders (PD) is mostly assessed in relation to axis1 disorders in spite of its high prevalence in clinical practice. It’s assessment in the prison community, a non-clinical setting, using the diagnostic and statistical manual (DSM-111-R) and the international classification of diseases (ICD-10) may reveal the natural pattern of axis-11 comorbidity and test the reliability of both instruments in assessing PD. Objectives of the study were to determine the pattern of comorbidity of PD in a non-clinical setting and to confirm the reliability of DSM-111-R and ICD-10 in assessing PD. Methods: Healthy prison inmates who consented to the study were interviewed using international personality disorder examination (IPDE), a semi structured questionnaire modified to conform to DSM-111-R and ICD-10 classifications and approved by World health organization (WHO). The data obtained was fed into the statistical package for social sciences (SPSS/PC+). Cross tabulation of variables using chi-square and t-tests. Agreement between both instruments was examined with kappa. Results: The study shows that ICD-10 is more likely to diagnose PD than DSM-111-R. Both instruments showed good concordance for schizoid, histrionic, and dependent PD, poor concordance for obsessive and borderline PD and very poor concordance for avoidant PD. The likelihood of having more than one axis-11 disorder is high lightened. Conclusions: Pattern of PD in the prison has been established. DSM-111-R and ICD-10 have been found reliable in assessing PD except for avoidant PD where they disagreed. The high rate of multiple PD diagnoses in prison inmates calls for functional health care programs in the prisons.